2016
DOI: 10.1016/j.cryobiol.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles of detergent resistant fractions of the plasma membrane in oat and rye in association with cold acclimation and freezing tolerance

Abstract: Cold acclimation (CA) results in alteration of the plasma membrane (PM) lipid composition in plants, which plays a crucial role in the acquisition of freezing tolerance via membrane stabilization. Recent studies have indicated that PM structure is consistent with the fluid mosaic model but is laterally non-homogenous and contains microdomains enriched in sterols, sphingolipids and specific proteins. In plant cells, the function of these microdomains in relation to CA and freezing tolerance is not yet fully und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 58 publications
5
20
0
4
Order By: Relevance
“…Acclimation capacity was correlated with changes in the content of TAGs (triacylglycerols), MGDG (monogalactosyldiacylglycerol), DGDG (digalactosyldiacylglycerol) and a GlcCer (Degenkolbe et al, 2012). Analysis of oat, rye and Arabidopsis lipid profiles during cold acclimation demonstrated that GlcCer contents decreased in the plasma membrane, whereas they were unchanged in microdomains (Minami et al, 2009;Takahashi et al, 2016). These changes could contribute to a greater hydration of the plasma membrane that could, in turn, increase membrane stability during cold stress.…”
Section: Sphingolipids As Structural Components In Response To Abiotimentioning
confidence: 99%
“…Acclimation capacity was correlated with changes in the content of TAGs (triacylglycerols), MGDG (monogalactosyldiacylglycerol), DGDG (digalactosyldiacylglycerol) and a GlcCer (Degenkolbe et al, 2012). Analysis of oat, rye and Arabidopsis lipid profiles during cold acclimation demonstrated that GlcCer contents decreased in the plasma membrane, whereas they were unchanged in microdomains (Minami et al, 2009;Takahashi et al, 2016). These changes could contribute to a greater hydration of the plasma membrane that could, in turn, increase membrane stability during cold stress.…”
Section: Sphingolipids As Structural Components In Response To Abiotimentioning
confidence: 99%
“…Therefore, perception of and response to a drop in temperature is essential for plants that originated in tropic and sub-tropic regions to deploy survival mechanisms and for those in temperate climatic zones to start the acclimation processes and prepare for upcoming freezing stress. Responses to cold under acclimating and freezing conditions are studied extensively on both genomic and proteomic levels [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, there is little or no information available on how plants sense temperature drops over a short time (i.e., seconds and minutes) and how they respond and form adaptive signals to the cold.…”
Section: Introductionmentioning
confidence: 99%
“…Обидва процеси врешті-решт призводять до пошкодження молекулярних клітин, що може сприяти розвитку різних патологічних станів та прискоренню процесів старіння (Ayala et al, 2014). ПОЛ є первинною реакцією рослинних клітин на дію стресів, що призводить до руйнування ліпідного комплексу мембран, порушуючи їхні транспортні функції, а також пригнічуючи процеси генерації енергії, що в кінцевому результаті знижує життєдіяльність клітин (Baraboi, 1991;Takahashi et al, 2016). Водночас ці процеси індукують стрес-захисні реакції, що мають важливе значення для відновлення та адаптації функціонуючих структур, внаслідок підвищення ефективності ферментативного та неферментативного антиоксидантного захисту та чіткого контролю вмісту активних кисневих радикалів, ліпідних пероксидів і каталізаторів пероксидазних реакцій (Zhu, 2016;Laxa et al, 2019).…”
Section: значення процесів ліпопероксидації у формуванні стрес-захиснunclassified